The Effect of Motivation and Discipline on Employee Performance at the Ministry of Transportation's Directorate of Ports - Totong Endang S; Elliana Sari (Ilomata International Journal of Social Science, 2019)
Motivation and work discipline are the important things in an organization, because theh are a factor which plays a role in obtaining the optimal work. With the motivation accompanied by good work discipline of the employees will greatly affect the personal performance which in the end the organizational goals will be easily achieved. This study aims to determine the effect of motivation and discipline on employee performance, both together and partially. The approach of this research is quantitative with a population of 149 and sample 108. Data collection using questionnaires and data analysis using t test and F test. The results showed motivation has an influence on the performance of the Directorate of Ports of the Ministry of Transportation's employees by 15.6%. Discipline has an influence on the performance of the Ministry of Transportation's Port Directorate's employees by 19.4%. Motivation and Discipline together have an influence of 27.6%.